Stimulating digital innovation for growth and inclusiveness: the role of policies for the successful diffusion of ICT - Reimsbach-Kounatze, Christian (Paris, 2016)
"This report analyses the importance of the adoption and the effective use of information and communication technologies (ICTs) for enabling digital innovation for growth and inclusiveness, and discusses the role of public policies in stimulating such adoption and use. Given the emergence of a new digital divide caused by a possible breakdown of the "diffusion machine", and given the strong interest of governments in furthering ICT adoption and use in particular by SMEs and disfavoured social groups, emphasis is put on policies stimulating ICT diffusion across society, i.e. ICT demand side policies."